Peritumoral administration of antigen-unstimulated bone marrow-derived dendritic cells inhibits tumour growth - Mendoza, L; Indrová, M; Hájková, R; Reinis, M; Smahel, M; Vonka, V; Bubeník, J; Jandlová, T (Folia biologica, 2000)
Murine BM cells from B6 mice were grown in vitro in medium supplemented with GM-CSF and IL-4 to differentiate DC from DC precursors. After 10 days of culture, approximately 20% of the cell population exhibited the characteristic morphology of BMDC. In cytofluorometric analysis the morphological changes of cells were accompanied by upregulation of the expression of the MHC class II, CD11c, CD80, and CD86 molecules. The BMDC were pulsed with a lysate of syngeneic MK16 carcinoma cells and used for in vitro activation of SC. Co-cultivation of the carcinoma lysate-pulsed BMDC with SC induced a proliferative response of the syngeneic SC. Priming of the proliferative responses was more efficient when the BMDC were grown in the presence of GM-CSF and IL-4 for 10 days than for 7 days. The in vivo effect of mature, tumour lysate-unstimulated BMDC was examined in mice carrying syngeneic MK16 carcinoma transplants. It has been found that local pretreatment with BMDC inhibits growth of a subsequent challenge inoculum of the MK16 cells. Similarly, treatment of mice carrying small MK16 tumours and of those with MK16 surgical minimal residual disease performed with BMDC significantly inhibited tumour growth. It can be concluded from these results that local concentration of mature BMDC at the tumour site can control the development and growth of the transplanted tumour inoculum.
Keywords: kokultivační techniky; Animals; transplantace buněk; Antigens, Neoplasm; Dendritic Cells; dendritické buňky; buňky kostní dřeně; Immunotherapy; buněčná diferenciace; Mice; test smíšené lymfocytární kultury; Cell Transplantation; Carcinoma; experimentální nádory; karcinom; myši; Lymphocyte Culture Test, Mixed; imunoterapie; Coculture Techniques; Bone Marrow Cells; Cell Differentiation; zvířata; antigeny nádorové; Neoplasms, Experimental